Perceived Convenience Towards Subscription Interest in Netflix: A Case Study of Consumers - Aryani Cahaya Putri; Nyoman Sri Subawa (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to examine the effects of content richness, service features, and perceived ease of use on subscription interest, with perceived convenience acting as a mediating variable among Netflix users. The research was conducted in Bali as an international tourism destination characterized by a high level of streaming service usage. A quantitative approach was employed using a survey method involving 100–150 respondents selected through purposive sampling. Data were collected through an online questionnaire utilizing a Semantic Differential scale (1–10) and analyzed using statistical techniques. The findings reveal that content richness, perceived ease of use, and perceived convenience have positive and significant effects on subscription interest, while service features do not exert a significant direct effect. Furthermore, content richness and service features significantly influence perceived convenience. Mediation analysis indicates that perceived convenience does not mediate the relationship between content richness and subscription interest, but it successfully mediates the effects of service features and perceived ease of use on subscription interest. These findings underscore the importance of user convenience in enhancing subscription interest in digital streaming services.